К истокам народных традиций - Павлова Е. В. (Сарапульская городская типография, 2016)
Экземпляры: аб. ЦБ (2017.21.12) / Инвентарный номер: 4033 / Сис.шифр: 63.52 / Авт.знак: К 11 / ГРНТИ: 18.46.45 / ББК: 63.52